Low temperature combustion of organic coal-water fuel droplets containing petrochemicals while soaring in a combustion chamber model; Thermal Science; Vol. 21, iss. 2 - Valiullin T. R. Timur Radisovich; Strizhak P. A. Pavel Alexandrovich; Shevyrev S. A. Sergey Aleksandrovich (2017, 2017)
Title screen